Comparison of Two Perceptual Methods for the Evaluation of Vowel Perturbation Produced by Jitter - Gurlekian, Jorge Alberto (2016)
Objectives: To explore perceptual evaluation of jitter produced by fundamental frequency (F0) variation in a sustained vowel /a/, using two different methods. One is based on listener's internal references and the other is based on external references provided by the experimenter. Methods:We used two methods: one is magnitude estimation-converging limits (ME-CL), which is close to the standard approach used by speech therapists when they use numerical estimations and their own standards, and other is intramodal matching procedure (IMP), where each matched stimulus is to be compared with a fixed-set matching stimuli. Systematic variations were introduced in vowel /a/ by Linear Prediction Coding synthesis using an F0 contour function obtained from a statistical jitter model. Six jitter values were used for each of two reference F0 values. Three groups of listeners were tested: expert speech therapists, speech therapy students, and naïve listeners. Results: Perceptual functions appear to be similar and linear for both methods as the theory predicts. The answers of all groups of listeners tested with ME-CL present higher standard deviations than for IMP. When subjects were tested with IMP, intrareliability and interreliability measurements show a significant improvement for both expert and naïve listeners. Conclusions: Both intraindividual and interindividual differences for expert speech therapists could be better managed when tested with an IMP than when they use numerical estimations and internal standards to evaluate vowel perturbation produced by jitter. This procedure could be the basis for the development of a clinical evaluation tool.